Modified control chart for monitoring the variance - Landim, Tiago Ruckert; Jardim, Felipe Schoemer; Oprime, Pedro Carlos (Brazilian Journal of Operations & Production Management, 2021)
ABSTRACT. Goal: The main objective of this research paper is to propose a chart, named Modified Control Chart, where the process variance () is allowed to be larger than the in-control variance value () until a maximum value (), as long as the process remains capable, in the sense that it produces a specified (tolerated) small fraction of non-conforming items. Design / Methodology / Approach: The research methodology was quantitative approach with statistical analysis of simulated data, to assess the practical impact of variance increase in process control in terms of quality requirements. Results: The analysis of the simulated data showed that by using the proposed Modified Control Chart the number of unnecessary interventions in the process could be decreased, contributing to improve its efficiency. Limitations of the investigation: The analysis assumed mean and variance known, which is unlikely to occur in real applications. Research considering unknown parameters is also in progress. Practical implications: The S2 Modified Control Chart detects only genuinely increases in the process variance, which significantly increase the rate of non-conforming items being produced, preventing unnecessary process stop and assessment for assignable causes if only a small increase in the process variance occurs, contributing for higher process efficiency and reduce costs. Originality / Value: This paper introduces a new control chart to monitor the variance of quality characteristics being produced by capable processes, preventing process overcontrol.